Towards fin de siecle: A time to revision Durkheim's sociology of education? - Paul Armstrong (Adult Education Research Conference, 1997)
This paper builds on earlier work on values and ethics that argued the need to re-vision the ideas of Emile Durkheim, by suggesting that the argument is supported by the notion of fin de siecle, which implies that the challenges of post-modernity are by no means new, and that there is evidence of a patter or even a cycle that would seem to re-appear at the end of each century. Approaching the 21st century and the millennium, the notion of fin de siecle has additional significance. But is it merely a matter of history repeating itself? And is this important to the educators of adults?